Detection and recognition of objects from mobile laser scanning point clouds : case studies in a road environment and power line corridor - Lehtomäki, Matti; Aalto-yliopiston perustieteiden korkeakoulu. Tietotekniikan laitos; Maanmittauslaitos. Kaukokartoitus ja fotogrammetria (Aalto University publication series, ISSN 1799-4934, 2021)
Kohteitten automaattinen havaitseminen ja tunnistaminen liikkuvalla laserkeilaimella kerätyistä pistepilvistä.
Keywords: laserkeilaus; data; tulkinta; automaatio; havaitseminen; tunnistaminen; algoritmit; laserskanning; tolkning (kognition); automation; perception; igenkännande; algoritmer; mobile laser scanning; point cloud; algorithm; automated interpretation; detection; recognition; classification; feature extraction; road; power line